Clinical phase III study of cimetropium bromide (DA3177) on the pain with upper urinary calculus a double-blind study in comparison with scopolamine butylbromide. DA3177 Study Group - Ohkawa, T (Hinyokika kiyo. Acta urologica Japonica, 1997)
A double-blind study was conducted to evaluate the efficacy, safety and usefulness of cimetropium bromide (DA3177) in the patients with pain caused by upper urinary calculus at a daily dose of 75 mg t.i.d. (Group D, 97 patients) in comparison with scopolamine butylbromide at a daily dose of 60 mg t.i.d. (Group B, 101 patients). According to patient's impression, the rate of "moderately improved" or better was significantly higher in Group D (68.7%) than in Group B (53.5%; Wilcoxon 2 sample test: p = 0.0044). For pain, the rate of "moderately improved" or better was 69.1% in Group D and 60.4% in Group B. In global improvement, the rate of "moderately improved" or better was significantly higher in Group D (70.1%) than in Group B (61.4%; Wilcoxon 2 sample test: p = 0.0469). The rate of "no problem in safety" showed no significant difference between Group D (91.5%) and Group B (93.3%). Adverse reactions occurred in 8.5% in Group D and 6.7% in Group B. The major adverse reactions were "dry mouth", "abdominal distension", "constipation" and "nausea". The rate of "useful" or better was 68.7% in Group D, and 60.4% in Group B. In conclusion, DA3177 was confirmed to be a useful drug for patient with pain caused by upper urinary calculus